Species richness and host-plant diversity are positively correlated in Coccidae - Lin, Y.P.; Gullan, P.J.; Cook, L.G. (ENTOMOLOGIA HELLENICA, 2010)
The interactions between insect herbivores and their hosts are among the most fundamental biological associations. Although there are many data available on the host associations of scale insects, there have been few attempts to synthesize the available information. Here we examine host associations of Coccidae, the third most species-rich family of scale insects. We compare host-plant data for most species of coccids that were available from online databases, especially ScaleNet, and the literature, with species richness estimates for host-plant families. Similar to most insect groups, coccids showed high host specialization with about 64% of species recorded from only a single plant family. Analysis of the relationship between species richness of host-plant families and the number of species of coccids recorded on these plants showed a significant positive correlation between host-plant species richness per angiosperm plant family and coccid species richness (P < 0.0001). This is expected under a null model in which host use is randomly distributed across families according to plant species richness of the families. However, the presence of several exceptions (Orchidaceae and Asteraceae in particular) warns that host associations in coccids might be more complex than the correlation analysis suggests.